Kalkulacja ruchów księżyca w 4Q208 i 4Q209 - Drawnel, Henryk (The Biblical Annals, 2015)
The article deals with two Qumran manuscripts of the Astronomical Book of Enoch. The discussion concentrates on the meaning of the arithmetical calculation contained in the Aramaic text. Previous interpretations of the whole calculation presented all the fractions as related to the illuminated surface of the mooon in its waxing and waning phase. Such explanations have to be abandoned. The calculation denotes periods of moon visibility on the sky during the day and during the night, while only one column refers to the amount of light assigned to the surface of the moon. Thus the whole calculation should be considered as an attempt to present in a schematic way the time of moon visibility, and as an attempt to base time computus on the movement of the moon.